2017
DOI: 10.1177/1420326x17736908
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde diffusion within crystalline and amorphous cellulose at different temperatures and electric fields: A molecular dynamics study

Abstract: To provide a microcosmic theoretical support for the reduction of formaldehyde in building material, the diffusion process was investigated by molecular dynamics simulation. In addition, the diffusion model of formaldehyde molecules in crystalline and amorphous cellulose was built, and diffusion coefficients at different temperatures and electric fields were studied. The simulation temperature was from 293 to 393 K and electric field was from 0 to 400 kV/m. Diffusion coefficient increased with greater temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…As for adsorption properties, in their molecular simulation of adsorption of various absorbates in cellulose, Da Silva Perez et al [73] found that the heat of adsorption for a large variety of aromatic compounds is consistent with experimental values; 84% of the adsorbate-cellulose couples displayed differences of less than 20% between the measured and predicted heats of adsorption. Xu and Chen [74] also found that PCFF predicts formaldehyde diffusion in cellulose showing a temperature-dependent self-diffusion coefficient in good agreement with experimental data. Overall, the research presented above shows that the PCFF forcefield can provide a reasonable, at least semi-quantitative, description of cellulose in terms of its density, mechanical, and adsorption properties.…”
Section: Polymer Consistent Force Field (Pcff)supporting
confidence: 66%
“…As for adsorption properties, in their molecular simulation of adsorption of various absorbates in cellulose, Da Silva Perez et al [73] found that the heat of adsorption for a large variety of aromatic compounds is consistent with experimental values; 84% of the adsorbate-cellulose couples displayed differences of less than 20% between the measured and predicted heats of adsorption. Xu and Chen [74] also found that PCFF predicts formaldehyde diffusion in cellulose showing a temperature-dependent self-diffusion coefficient in good agreement with experimental data. Overall, the research presented above shows that the PCFF forcefield can provide a reasonable, at least semi-quantitative, description of cellulose in terms of its density, mechanical, and adsorption properties.…”
Section: Polymer Consistent Force Field (Pcff)supporting
confidence: 66%